Midwife Care in Ny. W 29 Years with Placenta Retension at the Midwife Clinic of L. Pangaribuan Village Simantin Pane Dame - Yeni Trisna Purba (Science Midwifery, 2022)
The goal of development in the health sector towards a healthy Indonesia in 2015 is to increase awareness, willingness, and ability to live a healthy life for everyone so that the highest level of public health can be realized, so that it is an investment in improving the quality of human resources. Health development that has been carried out continuously in the last three decades has succeeded in significantly improving the health status of the community. Based on WHO research in Indonesia, the maternal mortality rate is 330/100,000 live births. This shows that the ability of obstetric services has not yet touched the community. Maternal mortality is estimated at around 16,500-17,500 per year (Manuaba, 2008). The study on the case of the third stage of labor in Mrs. W aged 29 years with retained placenta obtained subjective data with the main complaint that the mother was worried because the placenta had not yet been born, the mother felt tired and weak and the mother said that in the first delivery the placenta had been manual. While the objective data obtained data on general condition is weak, composmentis consciousness, TTV: BP: 110/70 mmHg, P: 78x/i, T: 36 0C, RR: 24x/i, umbilical cord does not extend at the vulva, bleeding ± 150 cc, unborn placenta after 30 min, weak contractions, TFU: at center level. Based on this, there is no gap between theory and practice